AIDS Funding for Federal Government Programs : FY1981-FY2006. (U.S. Congressional Research., 2005)
Reviews Federal discretionary and entitlement funding for HIV/AIDS programs from FY1981-FY2006. Discusses funding for HIV/AIDS research, prevention, and treatment programs at NIH, CDC, and the Health Resources and Services Administration, CMS HIV/AIDS treatment programs under Medicare and Medicaid, and funding for other Federal HIV/AIDS programs. Includes tables and graphs.